FACTORS INFLUENCING THE SPIRITUAL WORLDVIEW OF AN INDIVIDUAL IN CYBERSPACE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the flaws that negatively affect the spiritual maturity of individuals in cyberspace, taking into account the ideological attacks that spread ideas of aggression, destruction, depravity, and immorality within the spiritual realm of individuals in today's globalization era.